2020
DOI: 10.1103/physrevmaterials.4.045802
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of sodium ions in amorphousNa2Si2O5: Quasielastic neutron scattering andab initiomolecular dynamics s

Abstract: We have investigated the dynamics of Na ions in amorphous Na2Si2O5, a potential solid electrolyte material for Na-battery. We have employed quasielastic neutron scattering (QENS) technique in the amorphous Na2Si2O5 from 300 to 748 K to understand the diffusion pathways and relaxation timescales of Na atom dynamics. The microscopic analysis of the QENS data has been performed using ab-initio and classical molecular dynamics simulations (MD) to understand the Na-ion diffusion in the amorphous phase. Our experime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…181,182 Meanwhile, MD simulations were also performed to get a detailed understanding of the local atomic structures and their subsequent inuences on the ionic conductivity of the experiment synthesized sodium-based glasses, 183,184 and predict more new sodium-based glasses as the advanced electrolyte materials for solid-state sodium batteries. 185 Dive et al utilized the combination of AIMD simulations with 144 atoms and the classical MD simulations with $21 000 atoms to study the effect of local structure on the Na + ion transport in the Na 2 S-SiS 2 glass. 183 They found that the local short-range-order structures have great impacts on the distribution of stable Na + ion sites in the Na 2 S-SiS 2 glass.…”
Section: Sodium Sulfide-type Glassesmentioning
confidence: 99%
See 2 more Smart Citations
“…181,182 Meanwhile, MD simulations were also performed to get a detailed understanding of the local atomic structures and their subsequent inuences on the ionic conductivity of the experiment synthesized sodium-based glasses, 183,184 and predict more new sodium-based glasses as the advanced electrolyte materials for solid-state sodium batteries. 185 Dive et al utilized the combination of AIMD simulations with 144 atoms and the classical MD simulations with $21 000 atoms to study the effect of local structure on the Na + ion transport in the Na 2 S-SiS 2 glass. 183 They found that the local short-range-order structures have great impacts on the distribution of stable Na + ion sites in the Na 2 S-SiS 2 glass.…”
Section: Sodium Sulfide-type Glassesmentioning
confidence: 99%
“…181,182 Meanwhile, MD simulations were also performed to get a detailed understanding of the local atomic structures and their subsequent influences on the ionic conductivity of the experiment synthesized sodium-based glasses, 183,184 and predict more new sodium-based glasses as the advanced electrolyte materials for solid-state sodium batteries. 185…”
Section: Sodium Sulfide-type Glassesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, all the diffusion coefficients in Li 35 –GaSn and Li 50 –GaSn are in the order of 10 −7 cm 2 s −1 at a room temperature of 300 K. We have noticed that the diffusion coefficients for most liquid alloys are in the order of 10 −5 cm 2 s −1 52–55 and 10 −7 cm 2 s −1 for some amorphous states. 56 For example, AIMD simulations for liquid Al–Cu alloys by Jakse et al revealed that the self-diffusion coefficients D Al and D Cu are ∼0.1–0.6 Å 2 ps −1 , corresponding to (1–6) × 10 −5 cm 2 s −1 at 1000 K. For some room-temperature liquid alloys, the diffusion coefficient at the melting point can be in the order of 10 −6 cm 2 s −1 , such as the diffusion coefficient of Sn in Ga 91.6 Sn 8.4 at 300 K (see Table 1). The decrease in diffusion coefficients with the increase of Li content and their relatively small values imply that the lithiation process of Ga 91.6 Sn 8.4 will lead to a liquid–solid transformation, and the more the Li content is, the easier to form a solid-like structure.…”
Section: Resultsmentioning
confidence: 99%
“…We earlier performed 39 extensive ab-initio calculations of phonons, high-pressure phase stability, and thermal expansion behaviour in different phases of LiAlO2. We have also investigated the thermodynamic and ionic transport properties in several Li-and Na-based solid-ionic conductors using AIMD simulations and neutron scattering measurements [40][41][42][43][44] . Here, we focus on the diffusion mechanism of Li in various forms of LiAlO2 and investigated the structural and dynamical features relevant to Li diffusion.…”
Section: Introductionmentioning
confidence: 99%